Analysis and characterization of carbon nanotube - Azam, Mohd Asyadi; Raja Seman, Raja Noor Amalina (Woodhead Publishing, 2022)
The increasing demand for a foremost and inimitable invention in the area of nanotechnology is carbon nanotubes (CNT). CNT evolutions started in 1991. CNT nanomaterials were given great attention as viable electrode materials for energy storage devices such as supercapacitors and batteries due to its outstanding characteristics such as the unique 1D nanostructure, lightweight, large specific surface area, small in size, high conductivity, good strength, excellent flexibility, and chemical stability. CNT make useful in numerous fields of nanotechnology, biosensors, nanomedicine, and capacitors. CNT possess unique characteristics like mechanical, electrical, and optical. Large amounts of pristine nanotubes are required for commercial application. Characterization techniques of pristine and composites CNT are employed to examine morphological, thermal, qualitative, and elemental analysis. This present chapter covers the analysis and characterization of CNT in application of supercapacitor.